Analysis of Spatial Distribution Pattern and Driving Factors of Nature Reserves in Xinjiang - Yue Yang; Zhaoping Yang; Fang Han (Land)
Establishing nature reserves is fundamental to promoting ecological civilization and ensuring the ecological security of sustainable development, as well as a key strategy for maintaining the integrity of the national ecosystem. In recent years, with the enhancement in environmental awareness, the role of nature reserves in maintaining ecosystem stability, protecting biodiversity, and promoting sustainable development has become increasingly prominent. As a crucial ecological defense line in China, studying the spatial distribution and influencing factors of nature reserves in Xinjiang is vital for regional ecological protection and resource management. In this study, we focused on the nature reserves in Xinjiang and used kernel density and standard deviation ellipse analysis methods to examine data from 1980, 1990, 2000, 2010, and 2020 in order to reveal the dynamics of spatial distribution, clustering characteristics, and evolutionary patterns, providing a scientific basis for optimizing the spatial layout of nature reserves in Xinjiang. We also employed a geographical detector model to assess the main influencing factors. This study shows that the number, area, and types of nature reserves in Xinjiang have rapidly increased, forming an integrated system predominantly composed of nature reserves. Their spatial distribution exhibits a northeast–southwest orientation and a ring-centered clustering pattern. This spatial differentiation is the result of the interaction between natural and human factors, manifesting as an enhanced effect among these factors.